2017
DOI: 10.1080/02755947.2017.1336136
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Postrelease Predation for a Catch‐And‐Release Tropical Flats Fishery with a High Predator Burden

Abstract: Postrelease predation (PRP) of fishes released by anglers is a potentially significant contributor to overall mortality in recreational fisheries. We quantified PRP and examined the impacts of handling and release practices on Shortjaw Bonefish Albula glossodonta, a species of shallow‐water Pacific bonefish that supports a recreational fishery throughout its range and is emerging as recreationally important to the economy in Anaa Atoll, French Polynesia. We caught, released, and monitored the postrelease movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Friedlander et al . () analysed the length frequency distribution of the A. glossodonta stock in Palmyra Atoll, which provides an estimate of natural mortality (0.27) in a virgin population at a Pacific atoll with high predator densities similar to that of Anaa Atoll (Lennox et al ., ). Given the uncertainty regarding the estimation of these parameters, historic failure of analogous fisheries and traditional ecological knowledge of the community citing significant declines in A. glossodonta abundance, we recommend the more conservative Hoenig () estimate of 0.21 for both sexes in the assessment of this population.…”
Section: Discussionmentioning
confidence: 99%
“…Friedlander et al . () analysed the length frequency distribution of the A. glossodonta stock in Palmyra Atoll, which provides an estimate of natural mortality (0.27) in a virgin population at a Pacific atoll with high predator densities similar to that of Anaa Atoll (Lennox et al ., ). Given the uncertainty regarding the estimation of these parameters, historic failure of analogous fisheries and traditional ecological knowledge of the community citing significant declines in A. glossodonta abundance, we recommend the more conservative Hoenig () estimate of 0.21 for both sexes in the assessment of this population.…”
Section: Discussionmentioning
confidence: 99%
“…; Lennox et al. ). Furthermore, owing to the nature of this spawning‐aggregation fishery in which bonefish are not vulnerable to capture until sexual maturity, the lower bound of the size limit is naturally enforced by the reproductive biology of the species.…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, the establishment of a slot limit that protects both newly mature spawning females and megaspawners is a commonly utilized catch control in fisheries management (Froese 2004;Gwinn et al 2015). However, though theoretically effective, given the nature of the fishery where catches are brailed or netted from the traps in large quantities, we believe this solution will be hard to implement and there are many unanswered questions regarding the postrelease fate of these fish after interactions with humans (Coggins et al 2007;Lennox et al 2017). Furthermore, owing to the nature of this spawning-aggregation fishery in which bonefish are not vulnerable to capture until sexual maturity, the lower bound of the size limit is naturally enforced by the reproductive biology of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Most giant trevally recreational fisheries adopt catch-and-release practices, but we know nothing about post-release survival rates beyond this study, in which all five animals survived. All of these fish were hooked in the corner of the jaw, suggesting fly-fishing may be a conservative way to effectively catch and release these fish, but our sample size is too small to make definitive conclusions and further research is needed to determine how factors such as gear type, hook placement, fight time, and the angler's treatment of the fish affect their survival rates (Cooke and Philipp 2004;Cooke and Cowx 2006;Danylchuk et al 2007;Lennox et al 2017). Numerous physiologic changes from increased exercise, air exposure and tissue damage as a result of interactions with fishing gear can result in mortality (Brownscombe et al 2013(Brownscombe et al , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Other predators at Tetiaroa that could potentially threaten the survival of caught and released giant trevally include blacktip reef sharks (Carcharhinus melanopterus) and lemon sharks (Negaprion acutidens). Lennox et al (2017) revealed that similar predator-rich coral atolls can yield high rates of post-release predation of fish released by recreational anglers, emphasizing the need for anglers to handle species with care and that these environments require more attention from catch-and-release science.…”
Section: Discussionmentioning
confidence: 99%